Globular Shaped Polypyrrole Doped Well-Dispersed Functionalized Multiwall Carbon Nanotubes/Nafion Composite for Enzymatic Glucose Biosensor Application. Issue 1 (December 2017) - Shrestha, Bishnu; Ahmad, Rafiq; Shrestha, Sita; Park, Chan; Kim, Cheol
Abstract Herein, we report preparation of a bio-nanohybrid material of homogenously dispersed functionalized multiwall carbon nanotubes (f MWCNTs) in Nafion (Nf) doped with polypyrrole (PPy) and followed by one-stepin situ electrochemical polymerization along with glucose oxidase (GOx) on a platinum (Pt) electrode. The bioengineered Nf-GOx-f MWCNTs-PPy/Pt electrode showed excellent electrocatalytic performance to detect glucose with a high sensitivity (54.2 μAmM−1 cm−2 ) in linear range of up to 4.1 mM as well as a low detection limit of 5 μM (S/N = 3), response time within 4 s, good selectivity, stability, and practical applicability. It is our hope that the comprehensive results will contribute to design an efficient glucose biosensor with practical prospects for biomedical applications.